(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2023)
This article deals with equality and tax justice, under the terms addressed by the 1988 Constitution (the normative text), in comparison with what has been observed in practice for some time (the system in operation). The most relevant finding is that the Brazilian tax system has been working contrary to what was desired by the constituents of 1988, insofar as taxation affects the poorest significantly more intensely than those in better economic conditions. The tax system has also failed to provide a minimally acceptable level of wealth distribution in favor of the most needy, and it is even possible that it is contributing to further concentrate wealth in Brazil.